Superhydrophobicity Effects on Spheroid Formation and Polarization of Macrophages - María del Carmen Morán; Francesca Cirisano; Michele Ferrari (MDPI AG, 2024)
The interaction of biomaterials with the immune system is ruled by the action of macrophages. The surface features of these biomaterials, like wettability, which is an expression of chemical composition, texture, and geometry, can affect macrophages response. Such surface parameters can be then efficiently exploited to improve biocompatibility by lowering undesired immunological reactions and at the same time creating the substrate for positive interactions. In this work, the preparation and physicochemical characterization of highly water-repellent surfaces to develop and characterize 3D spheroids derived from monocyte-macrophages (RAW 264.7 cell line) has been carried out. As a measure of cell viability over time, the obtained aggregates have been transferred under standard 2D cell culture conditions. Significant changes on the morphology-associated polarization of the derived cellular entities have been evaluated at the nanoscale through 3D profilometry. The results suggested that the spheroid formation using highly repellent substrates induced the activation of M2-type cells. This simple and cost-effective approach can be used for preparing M2-based macrophages for regenerative purposes.